PERBEDAAN KECENDERUNGAN PERILAKU PROSOSIAL DITINJAU DARI PERAN GENDER PADA PENUMPANG KERETA API DI STASIUN CIKINI JAKARTA PUSAT (PSYCHOPEDIA : Jurnal Psikologi Universitas Buana Perjuangan Karawang, 2016)
This research aims to determine the difference in prosocial behavior trends in terms of gender roles in train passengers at Cikini station. The alternative hypothesis (Ha) in this study is that there are differences in prosocial behavior trends in terms of gender roles in train passengers at Cikini Station. The number of samples taken 120 sample and sampling techniques using accidental sampling. The data collection method uses a scale of prosocial behavior tendencies, and gender roles that refer to Likert scale assessments. After analyzing hypothetical data using One Way Anova, an F value of 3.893 was obtained with a significance level of 0.023 and p